Emissions trading with updated grandfathering. Entry/exit considerations and distributional effects - Knut Einar Rosendahl; Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2008)
Allocation of free emissions allowances may distort firms' incentives or have adverse distributional effects. Nevertheless, Böhringer and Lange (2005) show that in a closed emissions trading scheme with a fixed number of firms, a first-best outcome can be achieved if the base year for allocation is continually updated (i.e. updated grandfathering). In this paper we examine whether updated grandfathering alters the entry and exit conditions for firms compared to pure grandfathering, and how the distributional effects are affected. We find that updated grandfathering functions surprisingly similar to pure grandfathering: First, the incentives to entry and exit are identical under the two regimes. Second, the total value of free quotas to existing firms, based on emissions before the system starts, is identical under pure and updated grandfathering. In both cases, higher prices under updated grandfathering exactly match the shorter time period with free allowances. The only difference occurs when there is some combination of auction and pure or updated grandfathering, in which case the total value of free quotas will always be highest under pure grandfathering. Entry and exit incentives are still the same.
Keywords: H21; Q28; 330; Emission trading; Allocation of quotas; Quota prices